2008
DOI: 10.1542/peds.2008-0374
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Intramuscular Needle-Penetration Depth

Abstract: There is a substantial risk for overpenetration of the intramuscular layer when using current Centers for Disease Control and Prevention recommendations for vaccination needle lengths. We recommend a revision of the needle-length guidelines for thigh and shoulder injections to minimize the risk for needle overpenetration on the basis of the variability observed in the fat thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 18 publications
0
44
1
7
Order By: Relevance
“…Other potential risks associated with overpenetration includes pain and/or damage to the bone or periosteum and detachment of the needle from the syringe. 5,6 Upper arm intramuscular injections require penetration of the needle into the deltoid muscle layer by 5 mm or more to ensure that the injection is deposited into the muscle mass. 2 Accepted guidelines suggest that the needle should be inserted at 90 to the arm leaving 2e3 mm of needle exposed between the skin and the needle hub to avoid losing the needle within the arm in case the needle breaks at the hub.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential risks associated with overpenetration includes pain and/or damage to the bone or periosteum and detachment of the needle from the syringe. 5,6 Upper arm intramuscular injections require penetration of the needle into the deltoid muscle layer by 5 mm or more to ensure that the injection is deposited into the muscle mass. 2 Accepted guidelines suggest that the needle should be inserted at 90 to the arm leaving 2e3 mm of needle exposed between the skin and the needle hub to avoid losing the needle within the arm in case the needle breaks at the hub.…”
Section: Discussionmentioning
confidence: 99%
“…Potential risk of over-penetration include pain and damage to the bone or periosteum and detachment of the needle from the syringe. 5,6 A study conducted in the USA used ultrasound to determine the deltoid fat pad thickness in adult males and females. 2 It was found that women had a significantly thicker deltoid fat pad than men.…”
Section: Introductionmentioning
confidence: 99%
“…A study of MRI deltoid fat pads by Lippert found that with using 5/8-inch, 7/8-inch, or 1-inch needles for intramuscular deltoid injections would cause 11% (16 of 150), 55% (83 of 150), and 61% (92 of 150) of patients to experience overpenetration, respectively. 6 Based on Lippert's study, corroborated by an ultrasonographic study of deltoids by Koster 7 and…”
Section: Discussionmentioning
confidence: 90%
“…Lippert and Wall examined needle overpenetration through the muscle and into the bone or periosteum in children 2 months to 18 years old [36] . These authors determined that overpenetration of the deltoid muscle was a risk when immunizing children, and that needle length be selected according to the weight of the child.…”
Section: Overpenetrationmentioning
confidence: 99%